Detection of Collapse and Crystallization of Saccharide, Protein, and Mannitol Formulations by Optical Fibers in Lyophilization - Horn, Jacqueline; Friess, Wolfgang (Frontiers in Chemistry, 2018)
The collapse temperature (Tc) and the glass transition temperature of freeze-concentrated solutions (Tg’) as well as the crystallization behavior of excipients are important physicochemical characteristics which guide the cycle development in freeze-drying. The most frequently used methods to determine these values are differential scanning calorimetry (DSC) and freeze-drying microscopy (FDM). The objective of this study was to evaluate the optical fiber system (OFS) unit as alternative tool for the analysis of Tc, Tg’ and crystallization events. The OFS unit was also tested as a potential online monitoring tool during freeze-drying. Freeze/thawing and freeze-drying experiments of sucrose, trehalose, stachyose, mannitol and highly concentrated IgG1 and lysozyme solutions were carried out and monitored by the OFS. Comparative analyses were performed by DSC and FDM. OFS and FDM results correlated well. The crystallization behavior of mannitol could be monitored by the OFS during freeze/thawing as it can be done by DSC. Online monitoring of freeze-drying runs detected collapse of amorphous saccharide matrices. The OFS unit enabled the analysis of both Tc and crystallization processes, which is usually carried out by FDM and DSC. The OFS can hence be used as novel measuring device. Additionally, detection of these events during lyophilization facilitate online-monitoring. Thus the OFS is a new beneficial tool for the development and monitoring of freeze-drying processes.